"Testing the Whole Thing on Tape" : A Preliminary Insight into the Performative Dimensions of the J.R.R. Tolkien's Own Recording of the Homecoming of Beorhtnoth Beorhtelm's Son - Neubauer, Łukasz (Uniwersytet Wrocławski. Centrum Interdyscyplinarnych Badań Relacji między Kulturą Oralną i Piśmienniczą, 2019)
‘The Homecoming of Beorhtnoth’ may not be the best known work of Tolkien, but it has nonetheless managed to provoke a considerable amount of academic discussion, both on account of its literary merits and the critical light it sheds upon the concept of heroism. Apart from that, it is also unusual in that it came to be captured on tape twice within just a year of its publication, first by the author himself, and then, a few months later, by the BBC. The article seeks to examine only the first of these recordings (without, however, disregarding the latter), taking into consideration such performative traits as the use of distinct voices for each of the characters, sound effects produced by use of various domestic appliances and/or elements of furniture, chanting and declaiming funerary songs and prayers, as well as, no less significantly, different household and street noises which could be heard from time to time in the background.
Keywords: Tolkien, J. R. R. (1892-1973)